El centenario (1910) chileno y el rescate del pasado a través de sus hombres - María José Schneuer (Mélanges de la Casa de Velázquez)
During the centenary the Chilean elite strove to present the hundred years of existence as a success, adopting the discourse of superiority developed over the 19th century, to set themselves apart from their American peers and thus lay the foundations of a national identity. At the same time voices were raised announcing the existence of a national crisis. This paper seeks to throw light on the ways in which different actors from the past were harnessed to the various discourses on the nation and the rationales behind them. While the official celebrations used a view of the hero identified with the protagonists of independence, certain intellectuals, and also the conservative press, sought to aggrandise exceptional men as forgers of a better country, examples of virtues and values allegedly absent at the turn of the century, which urgently required regenerating. This attribution was one of the devices used to retrieve the national memory at a time of national crisis.